Penerapan SPK Menggunakan Metode Simple Additive Weighting (SAW) Seleksi Perekrutan Karyawan Bengkel - Karnadi, Very (LPPM STIKOM Tunas Bangsa, 2024)
PT X is a company operating in the automotive sector which provides various tools and two-wheeled motorbike parks. PT X is well known to customers both in the surrounding area and outside. To improve quality so that it responds quickly and is able to complete work according to targets, sufficient employees are needed. In recruitment, criteria are needed to match the targets and qualities required. However, the problem that often occurs today is that companies still experience difficulties in the employee recruitment process, this is caused by the many criteria factors in the selection process. To solve this problem, a Simple Additive Weighting (SAW) method is needed which is able to solve problems related to employee recruitment according to alternative criteria and the weight values used. The criteria used are 1. Experience, 2. Expertise, 3. Basic Ability Test 4. Responsibility and 5. Ethics. Based on the final score search results, the highest recruitment scores were obtained, namely Roby Sugara with a score of 0.95, recommendation 1, Agung Setang Budi with a score of 0.851, recommendation II and Benny Vernando with a score of 0.82, recommendation III. The decision making system using the SAW method is able to solve recruitment problems according to predetermined criteria.